Targeting Super-Enhancers as a Therapeutic Strategy for Cancer Treatment - He, Yi; Long, Wenyong; Liu, Qing (Frontiers in Pharmacology, 2019)
Super-enhancers (SEs) are large clusters of enhancers driving genes expression. In recent years, exciting new data provided insights in understanding the mechanism of SEs in many diseases including cancers. Many mechanisms involved in tumorigenesis and progression, from internal gene mutation and rearrangement to external damage and inducement, proved to be highly associated with SEs. And translocation, formation, deletion or duplication of SEs themselves could lead to tumor, too. It is documented that great amounts of oncogenic molecules and pathways in SEs’ downstream, which were tightly controlled by SEs. Moreover, clinical trials of novel SEs blockers like BETi and CDK7i has been launched, indicating SEs’ potential role in cancer therapy. In this review, we will highlight the molecular mechanism of SEs in cancer development and the potential new therapeutic strategy by targeting SEs for cancer treatment. It is hoped that targeting SEs will complement the traditional approaches and lead to more effective treatment for cancer patients.